The non-classical ArsR-family repressor PyeR (PA4354) modulates biofilm formation in Pseudomonas aeruginosa - Mac Aogáin, M.; Mooij, M.; McCarthy, R.; Plower, E.; Wang, Y.; Tian, Z.; Dobson, A.; Morrissey, J.; Adams, C.; O'Gara, Fergal (Society for General Microbiology, 2012)
PyeR (PA4354) is a novel member of the ArsR family of transcriptional regulators and modulates biofilm formation in Pseudomonas aeruginosa. Characterization of this regulator showed that it has negative autoregulatory properties and binds to a palindromic motif conserved among PyeR orthologues. These characteristics are in line with classical ArsR-family regulators, as is the fact that PyeR is part of an operon structure (pyeR-pyeM-xenB). However, PyeR also exhibits some atypical features in comparison with classical members of the ArsR family, as it does not harbour metal-binding motifs and does not appear to be involved in metal perception or resistance. Hence, PyeR belongs to a subgroup of non-classical ArsR-family regulators and is the second ArsR regulator shown to be involved in biofilm formation.